2019
DOI: 10.14201/orl.21241
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitación vestibular en la dependencia visual y somatosensorial.

Abstract: Conflicto de intereses: Los autores declaran no tener conflictos de intereses Imágenes: Los autores declaran haber obtenido las imágenes con el permiso de los pacientes Política de derechos y autoarchivo: se permite el autoarchivo de la versión post-print (SHERPA/RoMEO) Licencia CC BY-NC-ND. Licencia Creative Commons Atribución-NoComercial-SinDerivar 4.0 Internacional Universidad de Salamanca. Su comercialización está sujeta al permiso del editor PALABRAS CLAVE: vértigo visual; rehabilitación vestibular; habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
0
0
1
Order By: Relevance
“…On the other hand, our results are in line with the literature that states that greater visual dependence could be a response to proprioceptive deficits [48]. Alterations in the somatosensory system have been extensively studied in FMS [49,50].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, our results are in line with the literature that states that greater visual dependence could be a response to proprioceptive deficits [48]. Alterations in the somatosensory system have been extensively studied in FMS [49,50].…”
Section: Discussionsupporting
confidence: 93%
“…En otras ocasiones, la dependencia es somatosensorial y el paciente pierde con facilidad el equilibrio al alterarse la superficie de soporte. Bauer y cols., describen en este tema las características de la dependencia [8]. El tratamiento se basa en la terapia física, la realidad virtual y la estimulación optocinética progresiva, con el objetivo de desensibilizar al individuo y mejorar su sintomatología.…”
Section: Batuecas-caletrío á Et Alunclassified
“…Antidepressant medication prescriptions such as Selective Serotonin Reuptake Inhibitors (SSRIs) have also been used as pharmacological treatments for the improvement of chronic dizziness [19]. Vestibular Rehabilitation (VR) is used in functional vestibular disorders [20] and pretends to promote vestibular compensation by focusing on exercises that improve postural stability and facilitate habituation to conflicting sensory inputs (own movements or environmental situations that cause symptoms) in order to desensitize the patient, increase their tolerance to these sensory stimuli [21], decrease restrictions on activities of daily living and encourage social participation [13]. In addition, several studies have also reported improvements in subjective dizziness and postural control after VR supervised and delivered by physiotherapists [20,22].…”
Section: Introductionmentioning
confidence: 99%